Mind the Hype: A Critical Evaluation and Prescriptive Agenda for Research on Mindfulness and Meditation. (January 2018) - Van Dam, Nicholas T.; van Vugt, Marieke K.; Vago, David R.; Schmalzl, Laura; Saron, Clifford D.; Olendzki, Andrew; Meissner, Ted; Lazar, Sara W.; Kerr, Catherine E.; Gorchov, Jolie; Fox, Kieran C. R.; Field, Brent A.; et al.
During the past two decades, mindfulness meditation has gone from being a fringe topic of scientific investigation to being an occasional replacement for psychotherapy, tool of corporate well-being, widely implemented educational practice, and "key to building more resilient soldiers." Yet the mindfulness movement and empirical evidence supporting it have not gone without criticism. Misinformation and poor methodology associated with past studies of mindfulness may lead public consumers to be harmed, misled, and disappointed. Addressing such concerns, the present article discusses the difficulties of defining mindfulness, delineates the proper scope of research into mindfulness practices, and explicates crucial methodological issues for interpreting results from investigations of mindfulness. For doing so, the authors draw on their diverse areas of expertise to review the present state of mindfulness research, comprehensively summarizing what we do and do not know, while providing a prescriptive agenda for contemplative science, with a particular focus on assessment, mindfulness training, possible adverse effects, and intersection with brain imaging. Our goals are to inform interested scientists, the news media, and the public, to minimize harm, curb poor research practices, and staunch the flow of misinformation about the benefits, costs, and future prospects of mindfulness meditation.